المرونة النفسية وعلاقتها بالعبء المعرفي لدى تلاميذ السنة الثالثة ثانوي - بوعود فاطمة (جامعة الوادي - University of Eloued, 2025)
"ملخص الدراسة هدفت الدراسة الحالية الى الكشف عن علاقة المرونة النفسية بالعبء المعرفي لدى عينة من تلاميذ السنة الثالثة ثانوي بمتقنة عبد القادر الياجوري بقمار- ولاية الوادي- ودراسة الفروق بين افراد العينة في متغيري الدراسة تبعا لمتغير الجنس وبالاعتماد على المنهج الوصفي الارتباطي واستخدام مقياس المرونة النفسية "" لكونور دافيدسون ""ترجمة هشام عبد الحافظ ربابعة(2018)، ومقياس العبء المعرفي لحلمي الفيل(ّ2015)، تم تطبيق الدراسة الميدانية خلال الفصل الثاني للموسم الدراسي(2024/2025)، وبالاعتماد على أسلوب الحصر الشامل، تم اختيار عينة بلغ حجمها (155) فردا تمثل في جميع التلاميذ المتمدرسين بالسنة الثالثة ثانوي شعبة علوم تجريبية بمتقنة عبد القادر الياجوري -قمار- الـــوادي. باستخدام معامل الارتباط بيرسون واختبار ""T"" لعينتين مستقلتين توصلت الدراسة الى مجموعة من النتائج أهمها: • وجود علاقة طردية متوسطة ذات دلالة إحصائية بين درجات المرونة النفسية والعبء المعرفي لدى تلاميذ السنة الثالثة ثانوي عينة الدراسة. • عدم وجود فروق ذات دلالة إحصائية بين متوسطي درجات المرونة النفسية لدى تلاميذ السنة الثالثة ثانوي تعزى لمتغير الجنس. • عدم وجود فروق ذات دلالة إحصائية بين متوسطي درجات العبء المعرفي لدى تلاميذ السنة الثالثة ثانوي تعزى لمتغير الجنس. " Abstract The current study aimed to reveal the relationship between psychological flexibility and cognitive load among a sample of third-year secondary school students at Abdelkader El-Bagouri Technical School in Grammar - El Oued State - and to study the differences between sample members in the study variables according to the gender variable. Relying on the descriptive correlational approach and using the Connor Davidson Psychological Flexibility Scale, translated by Hisham Abdel Hafeez Rababa'a (2018), and the Pre-Dream Cognitive Load Scale (2015), the field study was implemented during the second semester of the academic year (2024/2025). Based on the comprehensive enumeration method, a sample size of (155) individuals were selected, representing all students enrolled in the year of the third secondary school, experimental sciences section, at Abdelkader El-Yajouri Technical School in Guemar - El Oued. Using Pearson's correlation coefficient and choosing ""T"" for two independent samples, the study reached a set of results, the most important of which are. - There is a moderate, statistically significant, direct relationship between psychological resilience scores and cognitive load among third-year secondary school students in the study sample. - There are no statistically significant differences between the average scores of psychological resilience among third-year secondary school students attributable to the gender variable. - There are no statistically significant differences between the average scores of cognitive loads among third-year secondary school students attributable to the gender variable.
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص إرشاد وتوجيه
Keywords: تلاميذ السنة الثالثة ثانوي; العبء المعرفي; المرونة النفسية; psychological resilience; cognitive load; third-year secondary school students